CONCEPTUAL INFORMATION IN LANGUAGES ACTIVATING STRUCTURES - Isakova Shohida; Khotamkulova Shahista (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article deals with the issues of the emergence of the information expressed by the concept with the help of a set of permanent and optional components. In the activation of conceptual information by means of verbal means, the action is characterized by the presence of a certain type of force, the person who implements it, the weapon of force, the necessary components of the concept are "subject", "object", "weapon of use of force", "act intended to be performed" etc.